Culturally Wetland Responsive Teaching to Improve Science Literacy and Wasaka Character - Syahmani Syahmani; Rilia Iriani; Muhammad Kusasi; Yogo Dwi Prasetyo; Hakki Norhasanah; Nur Farhana Abdul Rahman (Yayasan Keluarga Guru Mandiri, 2024)
Chemistry students still have low levels of scientific literacy, although in the era of the Industrial Revolution 4.0 and the transition to Society 5.0, students need these skills. An alternative for raising students' scientific literacy and character is the Culturally Wetland Responsive Teaching (CWRT) approach. This developmental research tested the validity, practicality, and effectiveness of e-modules based on CWRT for the colligative properties of solutions. The ADDIE development model was used for the research method. Both test and non-test instruments were used for data collection. The e-module was tested on 23 students from grades A1 and A2 in the Chemistry Education Study Program at a public university in South Kalimantan, Indonesia. The analysis showed that the e-modules were highly valid regarding content, presentation, language, and media feasibility. They were also highly practical in individual and small group tests, limited trials, and assessing lecturers' ability to use e-modules and manage classes. The modules were effective, as evidenced by the N-gain value of science literacy competence and the wasaka character of students in the high category. The results suggest that e-modules based on Culturally Wetland Responsive Teaching are valid, practical, and effective for teaching the colligative properties of solutions.